Pengaruh Kualitas Produk, Persepsi Harga, Store Atmosphere Terhadap Keputusan Pembelian Pada Forthis House Coffee Kota Samarinda - Ainnul Kharim; Muhammad Zaini (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Talking about coffee is always a conversation that attracts people's attention, especially coffee lovers. In Indonesia, coffee has become a popular trend because many people like this drink, this is in accordance with the Theory of Planned Behavior (TPB) and this theory is used as the grand theory in this research. This research aims to determine the influence of product quality, price perception, store atmosphere on purchasing decisions partially and simultaneously. This research uses quantitative research using an associative approach with a Likert scale. The sampling technique used was the Probability Sampling technique via Accidental Sampling with a sample of 100 Forthis House Coffee consumer respondents in Samarinda City. This research uses the Statistical Package for The Social Science (SPSS Version 26) to test the hypothesis. The research results show that there is a significant influence on price perceptions and store atmosphere, while product quality does not have a significant influence on purchasing decisions. However, simultaneously these three variables have a significant influence on purchasing decisions. So this research proves that consumers of Forthis House Coffee in Samarinda City really consider the price offered and really pay attention to the atmosphere of the cafe so they can make purchasing decisions about Forthis House Coffee in Samarinda City.